Winnie Mandela : the soul of South Africa - Meltzer, Milton, 1915-2009.; Marchesi, Stephen (New York, N.Y., U.S.A. : Viking Kestrel, 1986)
With an emphasis on her early years, covers the life of the South African woman who married a prominent fighter for racial equality in South Africa and later became a leader in her own right.
Keywords: Mandela, Winnie -- Juvenile literature; Mandela, Winnie; Civil rights workers -- South Africa -- Biography -- Juvenile literature; Civil rights workers; Blacks -- South Africa -- Biography; South Africa -- Race relations -- Juvenile literature; South Africa -- Race relations